Anti-inflammatory osteogenesis-promoting titanium-based implant as well as preparation method and application thereof
By constructing the TiO2 nanotube array layer on the surface of the titanium-based implant and loading IL-4, combining graft phylum molecules to regulate IL-4 release in response to changes in MMP concentration, the bacterial infection and sterile loosening of the titanium-based implant in the body were solved, and moderate inflammatory response and bone integration were achieved during bone healing.
Patent Information
- Application Number
- CN202510070877.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-11
AI Technical Summary
The surface emotion of the titanium-based implant in the body causes bacterial infection and sterile loosening, and the inflammatory response during bone healing is unmodified, affecting the osteogenic activity of the implant.
By constructing the TiO2 nanotube array layer in situ on the surface of the titanium substrate and loading interleukin-4 (IL-4) and grafting phylum molecule mPEG2000-PLGLAG-(PEG4)-C on its surface, the implant can respond to changes in matrix metalloproteinase (MMP) concentration in the microenvironment, regulate the release rate of IL-4, and dynamically regulate the immune response in the early stage of bone healing.
It achieves a short and moderate inflammatory response in the early stage of bone healing, promotes M2 polarization, enhances bone integration, reduces the risk of implant looseness, and improves the osteogenic activity of the implant.
Smart Images

Figure CN119792631A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of medical biotechnology, and in particular to an anti-inflammatory and osteopromoting titanium-based implant and a preparation method and application thereof. Background Art
[0002] Titanium-based implants are one of the most widely used orthopedic implant materials in clinical practice. The main problems caused by titanium-based implants due to their surface properties include bacterial infection and aseptic loosening. For orthopedic implant materials used for a long time, "aseptic loosening" caused by micro-motion between the implant and the surrounding bone, the generation of implant wear particles, stress shielding caused by mechanical mismatch between the implant and the bone, and insufficient bone integration at the interface between the implant and the bone will lead to implant failure. Therefore, how to improve the osteogenic activity of titanium-based implants and make them closely integrated with the surrounding tissues is one of the current research directions.
[0003] When biomaterials are implanted in the body, immune cells interact with the surface of the materials, triggering a series of complex inflammatory responses. Among these immune cells, macrophages play a vital role. They determine the implantation effect of biomaterials by releasing a variety of cytokines and growth factors, thus playing a central role in regulating the host immune response. Macrophages can be mainly divided into pro-inflammatory M1 phenotypes and healing-related M2 phenotypes. Adverse inflammatory responses, such as systemic activation of polymorphonuclear neutrophils (PMNs) and acute inflammation induced by LPS treatment, may lead to impaired fracture healing. Therefore, regulating the immune response by modulating the behavior of immune cells in the early stages of healing is currently regarded as a promising strategy for the development of advanced bone biomaterials.
[0004] In order to achieve an ideal microenvironment, the M1 or M2 phenotype has been regulated from multiple perspectives. If the inflammatory response (M1 polarization) is short and moderate, and can be transformed into the M2 phenotype in time, macrophages will release cytokines and chemokines to resolve inflammation, recruit osteoblasts, and activate the osteogenesis process, which will help the implant achieve better bone integration. Therefore, it is very beneficial to design titanium-based implants with immunomodulatory functions, so that M1 macrophages dominate in the early stage of bone healing, and can timely resolve inflammation and promote M2 polarization, and M2 macrophages dominate in the later stage to provide a favorable bone immune environment. Summary of the invention
[0005] In view of this, the purpose of the present invention is to provide an anti-inflammatory and osteopromoting titanium-based implant that can respond to changes in the concentration of matrix metalloproteinases (MMPs) in the surrounding microenvironment to regulate the release rate of interleukin-4 (IL-4), achieve dynamic regulation of bone healing immune response, accelerate wound repair, and promote bone integration.
[0006] The present invention is achieved through the following technical solutions:
[0007] An anti-inflammatory and osteopromoting titanium-based implant comprises a titanium substrate; a TiO2 nanotube array layer is in-situ constructed on the surface of the titanium substrate; IL-4 is loaded in the TiO2 nanotube array layer, and a gate molecule mPEG2000-PLGLAG-(PEG4)-C is grafted on the surface of the TiO2 nanotube array layer;
[0008] The structural formula of the gate molecule mPEG2000-PLGLAG-(PEG4)-C is as follows:
[0009]
[0010] The anti-inflammatory and osteopromoting titanium-based implant of the present invention constructs a TiO2 nanotube array layer loaded with interleukin-4 (IL-4) in situ on the surface of a titanium substrate, and simultaneously grafts a gate molecule mPEG2000-PLGLAG-(PEG4)-C on the surface of the TiO2 nanotube array layer by chemical grafting, so that the behavior of immune cells can be dynamically regulated in the early stage of bone healing after implantation in the body. M1 macrophages dominate in the early stage and maintain a short and moderate inflammatory response. In response to matrix metalloproteinases (MMPs) in the microenvironment, interleukin-4 (IL-4) is quickly released, M1 polarization is inhibited, inflammation is promptly eliminated, and M2 polarization is promoted, wound repair is accelerated, and bone integration is further promoted.
[0011] Preferably, the average diameter of the TiO2 nanotubes in the TiO2 nanotube array layer is 7-110 nm, and the tube depth is 150-1250 nm; more preferably, the average diameter of the TiO2 nanotubes in the TiO2 nanotube array layer is 40-90 nm, and the tube depth is 350-700 nm.
[0012] Preferably, the IL-4 loading in the anti-inflammatory and osteogenic titanium-based implant is 1.53 ng / cm 2 -42.56μg / cm 2 .
[0013] Preferably, the grafting amount of mPEG2000-PLGLAG-(PEG4)-C in the anti-inflammatory and osteogenic titanium-based implant is 1.05 molecules / nm 2 -259.50 molecules / nm 2 .
[0014] The gate molecule mPEG2000-PLGLAG-(PEG4)-C is grafted onto the surface of the TiO2 nanotube array layer through the reaction of thiol and titanium hydroxyl.
[0015] Preferably, the titanium substrate of the present invention includes a pure titanium substrate or a titanium alloy substrate.
[0016] The present invention provides a method for preparing the anti-inflammatory and osteogenic titanium-based implant, comprising the following steps:
[0017] (1) In-situ construction of a TiO2 nanotube array layer on the surface of a titanium substrate by anodization;
[0018] (2) preparing an IL-4 solution, dripping the IL-4 solution onto the surface of the TiO2 nanotube array layer on the titanium substrate, and absorbing the IL-4 solution into the interior of the TiO2 nanotubes using a negative pressure drug loading method to obtain a titanium-based implant loaded with IL-4;
[0019] (3) preparing mPEG2000-PLGLAG-(PEG4)-C solution, immersing the IL-4 loaded titanium-based implant in the mPEG2000-PLGLAG-(PEG4)-C solution, and reacting in the dark. After the reaction is completed, washing and drying are performed to prepare an anti-inflammatory and osteopromoting titanium-based implant.
[0020] Preferably, in step (1), the anodizing method comprises the following steps: using a titanium substrate as an anode, graphite as a cathode, and an electrolyte being a mixed aqueous solution of ammonium fluoride and ammonium sulfate, performing anodizing at a constant voltage, and after the reaction is completed, washing and drying to prepare a titanium substrate with an in-situ constructed TiO2 nanotube array layer on the surface; wherein the ammonium sulfate concentration of the electrolyte is 0.5-5 mol / L, the ammonium fluoride concentration is 0.1-2 wt%, and the pH value of the electrolyte is 4-6; the anodizing voltage is 5-30 V, the electrode spacing is 2-10 cm, and the reaction time is 0.5-2 h; the washing operation is washing with ethanol; and the drying operation is drying in a drying oven at 50-70°C.
[0021] Further preferably, the voltage of anodization is 15-25 V, the electrode spacing is 4-6 cm, and the reaction time is 0.5-1 h.
[0022] Further preferably, in step (1), the titanium substrate is first ultrasonically cleaned with acetone, ethanol, and deionized water in sequence, then treated with a 1-5% (v / v) dilute hydrofluoric acid solution for 1-5 min, and then used as an anode for anodization.
[0023] Preferably, in step (2), the preparation method of the IL-4 solution comprises the following steps: dissolving IL-4 in a PBS buffer solution containing 5% trehalose to prepare an IL-4 solution with a concentration of 0.1-200 μg / mL.
[0024] Preferably, in step (2), the negative pressure drug loading method is to use a vacuum dryer to draw a vacuum so that the IL-4 solution is absorbed into the interior of the TiO2 nanotubes.
[0025] Further preferably, in step (2), the steps of dripping the IL-4 solution and absorbing it into the interior of the TiO2 nanotubes are repeated to prepare a titanium-based implant loaded with IL-4. The steps are preferably repeated 1-20 times, more preferably 2-10 times.
[0026] Preferably, in step (3), the preparation method of the mPEG2000-PLGLAG-(PEG4)-C solution comprises the following steps: dissolving mPEG2000-PLGLAG-(PEG4)-C with deionized water to prepare a mPEG2000-PLGLAG-(PEG4)-C solution with a concentration of 50-200 μM.
[0027] Preferably, in step (3), the light-proof reaction time is 1-12 hours; the light-proof reaction is carried out at room temperature (20-30° C.).
[0028] Preferably, in step (3), the washing operation is to use deionized water to wash for 3-5 minutes; and the drying operation is to use nitrogen to blow dry.
[0029] The present invention also provides application of the anti-inflammatory and osteogenic titanium-based implant in the preparation of bone repair materials.
[0030] The present invention has the following beneficial effects:
[0031] The anti-inflammatory and osteogenic titanium-based implant of the present invention can respond to changes in the concentration of matrix metalloproteinases (MMPs) in the surrounding microenvironment to regulate the release rate of IL-4. In the early stage of bone healing, IL-4 is slowly released, M1 macrophages are dominant, and a short and moderate inflammatory response is maintained. With the response to MMPs in the microenvironment, IL-4 is quickly released, M1 polarization is inhibited, inflammation is promptly eliminated, and M2 polarization is promoted, wound repair is accelerated, bone integration is further promoted, and dynamic regulation of the immune response is achieved, providing a new strategy for promoting bone tissue regeneration through immune regulation. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 is a scanning electron microscope image of the surface nanotube layer of the anti-inflammatory and osteogenic titanium-based implant of Example 1;
[0033] Figure 2 is a scanning electron microscope image of a longitudinal section of the surface nanotube layer of the anti-inflammatory osteogenic titanium-based implant of Example 1;
[0034] Figure 3 is an in vitro release curve of the anti-inflammatory and osteogenic titanium-based implant of Example 1 in environments with different MMP concentrations;
[0035] Figure 4is a fluorescence intensity diagram of ROS in cells on the surface of an implant in the anti-inflammatory effect test of the anti-inflammatory and osteogenic titanium-based implant of Example 1;
[0036] Figure 5 This is a graph showing the absorbance results of CCK-8 cells in the cytotoxicity test of the anti-inflammatory and osteogenic titanium-based implant of Example 1;
[0037] Figure 6 is a scanning electron microscope image of the surface nanotube layer of the anti-inflammatory and osteogenic titanium-based implant of Example 2;
[0038] Figure 7 is a scanning electron microscope image of a longitudinal section of the surface nanotube layer of the anti-inflammatory osteogenic titanium-based implant of Example 2;
[0039] Figure 8 is an in vitro release curve of the anti-inflammatory and osteogenic titanium-based implant of Example 2 in environments with different MMP concentrations;
[0040] Fig. 9 is a scanning electron microscope image of the surface nanotube layer of the anti-inflammatory osteogenic titanium-based implant of Example 3;
[0041] Fig.10 is a scanning electron microscope picture of a longitudinal section of the surface nanotube layer of the anti-inflammatory osteogenic titanium-based implant of Example 3;
[0042] Fig.11 is an in vitro release curve of the anti-inflammatory and osteogenic titanium-based implant of Example 3 in environments with different MMP concentrations;
[0043] Fig.12 is a scanning electron microscope image of the surface nanotube layer of the anti-inflammatory osteogenic titanium-based implant of Example 4;
[0044] Fig.13 is a scanning electron microscope picture of a longitudinal section of the surface nanotube layer of the anti-inflammatory osteogenic titanium-based implant of Example 4;
[0045] Fig.14 is a scanning electron microscope image of the surface nanotube layer of the anti-inflammatory osteogenic titanium-based implant of Example 5;
[0046] Fig.15 is a scanning electron microscope picture of a longitudinal section of the surface nanotube layer of the anti-inflammatory osteogenic titanium-based implant of Example 5;
[0047] Fig.16 is a scanning electron microscope image of the surface nanotube layer of the anti-inflammatory osteogenic titanium-based implant of Example 6;
[0048] Fig.17is a scanning electron microscope image of a longitudinal section of the surface nanotube layer of the anti-inflammatory osteogenic titanium-based implant of Example 6;
[0049] Fig.18 is a scanning electron microscope image of the surface nanotube layer of the anti-inflammatory osteogenic titanium-based implant of Example 7;
[0050] Fig.19 is a scanning electron microscope picture of a longitudinal section of the surface nanotube layer of the anti-inflammatory osteogenic titanium-based implant of Example 7;
[0051] Fig. 20 is a scanning electron microscope image of the surface nanotube layer of the anti-inflammatory osteogenic titanium-based implant of Example 8;
[0052] Fig.21 is a scanning electron microscope picture of a longitudinal section of the surface nanotube layer of the anti-inflammatory osteogenic titanium-based implant of Example 8;
[0053] Fig. 22 is a scanning electron microscope image of the surface nanotube layer of the anti-inflammatory osteogenic titanium-based implant of Example 9;
[0054] Fig.23 is a scanning electron microscope image of a longitudinal section of the surface nanotube layer of the anti-inflammatory osteogenic titanium-based implant of Example 9;
[0055] Fig.24 is a scanning electron microscope image of the surface nanotube layer of the anti-inflammatory osteogenic titanium-based implant of Example 10;
[0056] Fig.25 is a scanning electron microscope picture of a longitudinal section of the surface nanotube layer of the anti-inflammatory osteogenic titanium-based implant of Example 10;
[0057] Fig.26 It is the in vitro release curve of the titanium-based implant of Comparative Example 1 in a PBS solution environment. DETAILED DESCRIPTION
[0058] In order to elaborate on the technical content, achieved purpose and effect of the present invention, the technical scheme of the present invention is clearly and completely described below in combination with the embodiments and with the accompanying drawings, but the described embodiments are only part of the embodiments of the present invention, and the implementation and protection of the present invention are not limited thereto. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. It should be pointed out that if there are processes that are not particularly described in detail below, they can be realized or understood by those skilled in the art with reference to the prior art. If the manufacturer is not indicated for the reagents or instruments used, it is regarded as a conventional product that can be purchased commercially.
[0059] Example 1
[0060] (1) The titanium substrate was ultrasonically cleaned in acetone, ethanol, and deionized water for 5 minutes each, and then treated with a 5% (v / v) dilute hydrofluoric acid solution for 4 minutes. The titanium substrate was used as an anode, graphite was used as a cathode, and the electrolyte was a mixed aqueous solution of ammonium fluoride and ammonium sulfate (ammonium sulfate concentration was 1 mol / L, ammonium fluoride concentration was 1 wt%, pH value was 5). The anodization was performed for 30 minutes at a voltage of 20 V and an electrode spacing of 5 cm. After the reaction was completed, the substrate was cleaned with ethanol and dried in a drying oven at 60° C. to prepare a titanium substrate with an in-situ constructed TiO2 nanotube array layer on the surface;
[0061] (2) Dissolving IL-4 (PeproTech, catalog number: 214-14) in a PBS buffer solution containing 5% trehalose to prepare an IL-4 solution with a concentration of 1 μg / mL; placing the titanium substrate with an in-situ constructed TiO2 nanotube array layer on the surface obtained in step (1) in a vacuum desiccator, dripping 50 μL of the IL-4 solution on the surface, and applying vacuum to absorb the IL-4 into the TiO2 nanotubes; repeating the steps of dripping the IL-4 solution and absorbing it into the TiO2 nanotubes three times to obtain a titanium-based implant loaded with IL-4;
[0062] (3) Dissolve mPEG2000-PLGLAG-(PEG4)-C (Shanghai Qiangyao Biotechnology Co., Ltd., catalog number: 04010077270) in deionized water to prepare a solution with a concentration of 200 μM, immerse the titanium-based implant loaded with IL-4 in step (2) in the mPEG2000-PLGLAG-(PEG4)-C solution, and react for 4 h at room temperature (26°C) in the dark. After the reaction, wash with deionized water for 3 min and blow dry with nitrogen to prepare an anti-inflammatory and osteogenic titanium-based implant, with an IL-4 loading of 49.50 ng / cm 2 ; The grafting amount of mPEG2000-PLGLAG-(PEG4)-C is 19.50 molecules / nm 2 .
[0063] The surface morphology of the titanium nanotubes in the anti-inflammatory and osteogenic titanium-based implant of Example 1 was observed by scanning electron microscopy. Figure 1 , Figure 2 As shown, the average diameter of the nanotubes is 78 nm and the depth is 511 nm.
[0064] IL-4 release rate test of anti-inflammatory and osteogenic titanium-based implants:
[0065] The anti-inflammatory and osteogenic titanium-based implant was immersed in PBS solution and placed on a constant temperature shaker (37°C, 85rpm). Three groups of parallel control experiments were set up. 1 mL of solution was taken as the test sample at specific time points of 1, 2, 4, 10, 24, 48, 72, 96, 120, 144, 168, 192, 216, 240, 264, 288, 312, and 336 hours. Among them, MMP was added at 72 hours (the final concentrations of MMP in the three test groups were 0 μg / mL, 1 μg / mL, and 5 μg / mL, respectively, to simulate the physiological microenvironment with different MMP concentrations). The ELISA kit was used to determine the IL-4 release of the anti-inflammatory and osteogenic titanium-based implant at each time point. The results are shown in Figure 2. Figure 3 As shown, it can be seen that in the PBS solution without MMP, the IL-4 release of the anti-inflammatory and osteogenic titanium-based implant is low; while in the PBS solution with MMP concentrations of 1μg / mL and 5μg / mL, the anti-inflammatory and osteogenic titanium-based implant releases IL-4 slowly before 72h, then IL-4 is released rapidly, the IL-4 concentration in the solution increases significantly, and the IL-4 concentration in the solution tends to be stable after 192h; increasing the MMP concentration can accelerate the release of IL-4. It shows that the anti-inflammatory and osteogenic titanium-based implant of the present invention can reduce the unnecessary release of IL-4 in a normal physiological microenvironment without MMP; in a microenvironment where the MMP concentration increases after bone injury, IL-4 is released slowly in the early stage, and the effect of M0 polarization to M2 is not produced, and M1 macrophages are dominant, while in the later stage, the MMP concentration increases, and IL-4 is released in a rapid response, inhibiting M1 polarization and promoting M0 polarization to M2, thereby achieving dynamic regulation of the immune response in the early stage of bone healing (maintaining a short and moderate inflammatory response (M1 polarization) and timely converting to M2 phenotype), providing a better immune microenvironment, and further promoting osteogenesis.
[0066] Anti-inflammatory effect test of anti-inflammatory titanium-based implants:
[0067] RAW264.7 cells were planted on the surface of the implant, and lipopolysaccharide (LPS) was added to stimulate the RAW264.7 cells to induce an inflammatory response. The generation of intracellular ROS increased, and the fluorescent probe DCFH-DA was used to detect the intracellular ROS level (DCFH-DA can freely pass through the cell membrane. When it enters the cell, it will be hydrolyzed to produce DCFH. The ROS in the cell can oxidize the originally non-fluorescent DCFH into green fluorescent DCF, and its fluorescence intensity is proportional to the intracellular ROS level). Testing the fluorescence intensity with a fluorescent microplate reader can illustrate the anti-inflammatory effect of the implant.
[0068] The implant density was 2×10 4RAW264.7 cells were stimulated by adding 100 ng / mL of LPS, wherein the anti-inflammatory and osteogenic titanium-based implant experimental group of Example 1 was also added with MMP (final concentration of 5 μg / mL); a blank control group (with an implant density of 2×10 4 RAW264.7 cells were cultured for 24 h without LPS stimulation. The intracellular ROS level was detected. Figure 4 As shown. The results show that the fluorescence intensity of the cells on the surface of the anti-inflammatory and osteogenic titanium-based implant of Example 1 is significantly lower than that of the unmodified titanium-based implant, and is close to that of the blank control group. The anti-inflammatory and osteogenic titanium-based implant of the present invention can release IL-4 in response to changes in MMP concentration, thereby inhibiting M1 and reducing the generation of ROS by 92%, and has an anti-inflammatory effect.
[0069] Cytotoxicity testing of anti-inflammatory and osteogenic titanium-based implants:
[0070] The implant density on the unmodified titanium-based implant and the anti-inflammatory and osteogenic titanium-based implant of Example 1 was 1×10 4 The cells were subjected to CCK-8 assay. On days 1, 3, and 5, the absorbance of each sample at 450 nm was tested. The results are as follows Figure 5 As shown, the absorbance value of the anti-inflammatory and osteogenic titanium-based implant group of Example 1 is higher than that of the unmodified titanium-based implant group, indicating that the anti-inflammatory and osteogenic titanium-based implant of the present invention has good biocompatibility and does not produce cytotoxicity.
[0071] Example 2
[0072] (1) The titanium substrate was ultrasonically cleaned in acetone, ethanol, and deionized water for 5 minutes each, and then treated with a 5% (v / v) hydrofluoric acid dilute solution for 4 minutes. The titanium substrate was used as an anode, graphite was used as a cathode, and the electrolyte was a mixed aqueous solution of ammonium fluoride and ammonium sulfate (ammonium sulfate concentration was 1 mol / L, ammonium fluoride concentration was 0.5 wt%, pH value was 5). The anodization was performed for 30 minutes at a voltage of 10 V and an electrode spacing of 5 cm. After the reaction was completed, the titanium substrate was cleaned with ethanol and dried in a drying oven at 60° C. to prepare a titanium substrate with an in-situ constructed TiO2 nanotube array layer on the surface;
[0073] (2) Dissolving IL-4 (PeproTech, catalog number: 214-14) in a PBS buffer solution containing 5% trehalose to prepare an IL-4 solution with a concentration of 3 μg / mL; placing the titanium substrate with an in-situ constructed TiO2 nanotube array layer on the surface obtained in step (1) in a vacuum desiccator, dripping 50 μL of the IL-4 solution on the surface, and vacuuming the IL-4 to absorb it into the TiO2 nanotubes; repeating the steps of dripping the IL-4 solution and absorbing it into the TiO2 nanotubes twice to obtain a titanium-based implant loaded with IL-4;
[0074] (3) Dissolve mPEG2000-PLGLAG-(PEG4)-C (Shanghai Qiangyao Biotechnology Co., Ltd., catalog number: 04010077270) in deionized water to prepare a solution with a concentration of 200 μM, immerse the titanium-based implant loaded with IL-4 in step (2) in the mPEG2000-PLGLAG-(PEG4)-C solution, and react for 4 h at room temperature (26°C) in the dark. After the reaction, wash with deionized water for 3 min and blow dry with nitrogen to prepare an anti-inflammatory and osteogenic titanium-based implant with an IL-4 loading of 67.22 ng / cm 2 ; The grafting amount of mPEG2000-PLGLAG-(PEG4)-C is 19.50 molecules / nm 2 .
[0075] The surface morphology of the titanium nanotubes in the anti-inflammatory and osteogenic titanium-based implant of Example 2 was observed by scanning electron microscopy. Figure 6 , Figure 7 As shown, the average diameter of the nanotubes is 28 nm and the depth is 267 nm.
[0076] IL-4 release rate test of anti-inflammatory and osteogenic titanium-based implants:
[0077] PBS solutions with MMP (Sigma-Aldrich, catalog number: M9445) concentrations of 0 μg / mL, 1 μg / mL, and 5 μg / mL were prepared to simulate the physiological microenvironment of different MMP concentrations. The anti-inflammatory and osteogenic titanium-based implant of Example 2 was immersed in PBS solutions containing different concentrations of MMP and placed on a constant temperature shaker (37°C, 85 rpm). At specific time points of 1, 2, 4, 10, 24, 48, 72, 96, 120, 144, 168, 192, 216, 240, 264, 288, 312, and 336 h, 1 mL of the solution was taken as the test sample, and the IL-4 release of the anti-inflammatory and osteogenic titanium-based implant was determined using an ELISA kit. The results are shown in Figure 2. Figure 8As shown, it can be seen that in the PBS solution without MMP, the IL-4 release of the anti-inflammatory and osteogenic titanium-based implant is low; while in the PBS solution with MMP concentrations of 1μg / mL and 5μg / mL, the anti-inflammatory and osteogenic titanium-based implant can respond to MMP, IL-4 is released rapidly, and the IL-4 concentration in the solution is significantly increased. When the MMP concentration increases from 1μg / mL to 5μg / mL, the IL-4 release rate is similar, with no significant difference.
[0078] Anti-inflammatory effect test of anti-inflammatory and osteogenic titanium-based implant: The anti-inflammatory effect test of the anti-inflammatory and osteogenic titanium-based implant of Example 2 was carried out using the same test method as Example 1. The results showed that it was able to respond to the MMP of the surrounding microenvironment to regulate the release of IL-4, inhibit the M1 polarization of macrophages, reduce the generation of ROS, and have an anti-inflammatory effect.
[0079] Example 3
[0080] (1) The titanium substrate was ultrasonically cleaned in acetone, ethanol, and deionized water for 5 minutes each, and then treated with a 5% (v / v) hydrofluoric acid dilute solution for 4 minutes. The titanium substrate was used as the anode, graphite was used as the cathode, and the electrolyte was a mixed aqueous solution of ammonium fluoride and ammonium sulfate (ammonium sulfate concentration was 2 mol / L, ammonium fluoride concentration was 1 wt%, pH value was 5). The anodization was performed for 30 minutes at a voltage of 25 V and an electrode spacing of 5 cm. After the reaction was completed, the substrate was cleaned with ethanol and dried in a drying oven at 60° C. to prepare a titanium substrate with an in-situ constructed TiO2 nanotube array layer on the surface;
[0081] (2) Dissolving IL-4 (PeproTech, catalog number: 214-14) in a PBS buffer solution containing 5% trehalose to prepare an IL-4 solution with a concentration of 5 μg / mL; placing the titanium substrate with an in-situ constructed TiO2 nanotube array layer on the surface obtained in step (1) in a vacuum desiccator, dripping 50 μL of the IL-4 solution on the surface, and vacuuming the IL-4 to absorb it into the TiO2 nanotubes; repeating the steps of dripping the IL-4 solution and absorbing it into the TiO2 nanotubes twice to obtain a titanium-based implant loaded with IL-4;
[0082] (3) Dissolve mPEG2000-PLGLAG-(PEG4)-C (Shanghai Qiangyao Biotechnology Co., Ltd., catalog number: 04010077270) in deionized water to prepare a solution with a concentration of 150 μM, immerse the titanium-based implant loaded with IL-4 in step (2) in the mPEG2000-PLGLAG-(PEG4)-C solution, and react for 4 h at room temperature (26°C) in the dark. After the reaction, wash with deionized water for 3 min and blow dry with nitrogen to prepare an anti-inflammatory and osteogenic titanium-based implant, and the IL-4 loading amount is 159.75 ng / cm 2; The grafting amount of mPEG2000-PLGLAG-(PEG4)-C is 15.42 molecules / nm 2 .
[0083] The surface morphology of the titanium nanotubes in the anti-inflammatory and osteogenic titanium-based implant of Example 4 was observed by scanning electron microscopy. Fig. 9 , Fig.10 As shown, the average diameter of the nanotubes is 92 nm and the depth is 912 nm.
[0084] IL-4 release rate test of anti-inflammatory and osteogenic titanium-based implants:
[0085] PBS solutions with MMP (Sigma-Aldrich, catalog number: M9445) concentrations of 0 μg / mL, 1 μg / mL, and 5 μg / mL were prepared to simulate the physiological microenvironment of different MMP concentrations. The anti-inflammatory and osteogenic titanium-based implant of Example 3 was immersed in PBS solutions containing different concentrations of MMP and placed on a constant temperature shaker (37°C, 85 rpm). At specific time points of 1, 2, 4, 10, 24, 48, 72, 96, 120, 144, 168, 192, 216, 240, 264, 288, 312, and 336 h, 1 mL of the solution was taken as the test sample, and the IL-4 release of the anti-inflammatory and osteogenic titanium-based implant was determined using an ELISA kit. The results are shown in Figure 2. Fig.11 As shown, it can be seen that in the PBS solution without MMP, the IL-4 release of the anti-inflammatory and osteogenic titanium-based implant is low; while in the PBS solution with MMP concentrations of 1μg / mL and 5μg / mL, the anti-inflammatory and osteogenic titanium-based implant can respond to MMP, IL-4 is released rapidly, and the IL-4 concentration in the solution is significantly increased. When the MMP concentration increases from 1μg / mL to 5μg / mL, the IL-4 release rate is similar, with no significant difference.
[0086] Anti-inflammatory effect test of anti-inflammatory titanium-based implants:
[0087] The anti-inflammatory and osteogenic titanium-based implant of Example 3 was tested for its IL-4 anti-inflammatory effect using the same testing method as Example 1. The results showed that it was able to respond to the MMP in the surrounding microenvironment to regulate the release of IL-4, inhibit the M1 polarization of macrophages, reduce the generation of ROS, and had an anti-inflammatory effect.
[0088] Example 4
[0089] (1) The titanium substrate was ultrasonically cleaned in acetone, ethanol, and deionized water for 5 minutes each, and then treated with a 5% (v / v) dilute hydrofluoric acid solution for 4 minutes. The titanium substrate was used as an anode, graphite was used as a cathode, and the electrolyte was a mixed aqueous solution of ammonium fluoride and ammonium sulfate (ammonium sulfate concentration was 0.5 mol / L, ammonium fluoride concentration was 0.1 wt%, pH value was 5). The anodization was performed for 30 minutes at a voltage of 20 V and an electrode spacing of 5 cm. After the reaction was completed, the titanium substrate was cleaned with ethanol and dried in a drying oven at 60° C. to prepare a titanium substrate with an in-situ constructed TiO2 nanotube array layer on the surface;
[0090] (2) Dissolving IL-4 (PeproTech, catalog number: 214-14) in a PBS buffer solution containing 5% trehalose to prepare an IL-4 solution with a concentration of 100 μg / mL; placing the titanium substrate with an in-situ constructed TiO2 nanotube array layer on the surface obtained in step (1) in a vacuum desiccator, dripping 50 μL of the IL-4 solution on the surface, and applying vacuum to absorb the IL-4 into the TiO2 nanotubes; repeating the steps of dripping the IL-4 solution and absorbing it into the TiO2 nanotubes 20 times to obtain a titanium-based implant loaded with IL-4;
[0091] (3) Dissolve mPEG2000-PLGLAG-(PEG4)-C (Shanghai Qiangyao Biotechnology Co., Ltd., catalog number: 04010077270) in deionized water to prepare a solution with a concentration of 150 μM, immerse the titanium-based implant loaded with IL-4 in step (2) in the mPEG2000-PLGLAG-(PEG4)-C solution, and react for 10 h at room temperature (26°C) in the dark. After the reaction, wash with deionized water for 3 min and blow dry with nitrogen to prepare an anti-inflammatory and osteogenic titanium-based implant, wherein the loading amount of IL-4 is 20.67 μg / cm 2 ; The grafting amount of mPEG2000-PLGLAG-(PEG4)-C is 35.50 molecules / nm 2 .
[0092] The surface morphology of the titanium nanotubes in the anti-inflammatory and osteogenic titanium-based implant of Example 2 was observed by scanning electron microscopy. Fig.12 , Fig.13 As shown, the average diameter of the nanotubes is 88 nm and the depth is 536 nm.
[0093] The anti-inflammatory and osteogenic titanium-based implant of Example 4 was subjected to IL-4 release rate test and anti-inflammatory effect test. The test method was the same as that of Example 1. The results showed that it was able to respond to the MMP of the surrounding microenvironment to regulate the release of IL-4, inhibit the M1 polarization of macrophages, reduce the generation of ROS, and have an anti-inflammatory effect.
[0094] Example 5
[0095] (1) The titanium substrate was ultrasonically cleaned in acetone, ethanol, and deionized water for 5 minutes each, and then treated with a 5% (v / v) dilute hydrofluoric acid solution for 4 minutes. The titanium substrate was used as an anode, graphite was used as a cathode, and the electrolyte was a mixed aqueous solution of ammonium fluoride and ammonium sulfate (ammonium sulfate concentration was 0.5 mol / L, ammonium fluoride concentration was 2 wt%, pH value was 5). The anodization was performed for 30 minutes at a voltage of 15 V and an electrode spacing of 5 cm. After the reaction was completed, the titanium substrate was cleaned with ethanol and dried in a drying oven at 60° C. to prepare a titanium substrate with an in-situ constructed TiO2 nanotube array layer on the surface;
[0096] (2) Dissolving IL-4 (PeproTech, catalog number: 214-14) in a PBS buffer solution containing 5% trehalose to prepare an IL-4 solution with a concentration of 10 μg / mL; placing the titanium substrate with an in-situ constructed TiO2 nanotube array layer on the surface obtained in step (1) in a vacuum desiccator, dripping 50 μL of the IL-4 solution on the surface, and applying vacuum to absorb the IL-4 into the TiO2 nanotubes; repeating the steps of dripping the IL-4 solution and absorbing it into the TiO2 nanotubes 10 times to obtain a titanium-based implant loaded with IL-4;
[0097] (3) Dissolve mPEG2000-PLGLAG-(PEG4)-C (Shanghai Qiangyao Biotechnology Co., Ltd., catalog number: 04010077270) in deionized water to prepare a solution with a concentration of 1000 μM, immerse the titanium-based implant loaded with IL-4 in step (2) in the mPEG2000-PLGLAG-(PEG4)-C solution, and react for 12 h at room temperature (26°C) in the dark. After the reaction, wash with deionized water for 3 min and blow dry with nitrogen to prepare an anti-inflammatory and osteogenic titanium-based implant with an IL-4 loading of 1.51 μg / cm 2 ; The grafting amount of mPEG2000-PLGLAG-(PEG4)-C is 259.50 molecules / nm 2 .
[0098] The surface morphology of the titanium nanotubes in the anti-inflammatory and osteogenic titanium-based implant of Example 4 was observed by scanning electron microscopy. Fig.14 , Fig.15 As shown, the average diameter of the nanotubes is 41 nm and the depth is 371 nm.
[0099] The anti-inflammatory and osteogenic titanium-based implant of Example 5 was subjected to IL-4 release rate test and anti-inflammatory effect test, and the test method was the same as that of Example 1. The results showed that it was able to respond to the MMP of the surrounding microenvironment to regulate the release of IL-4, inhibit the M1 polarization of macrophages, reduce the generation of ROS, and have an anti-inflammatory effect.
[0100] Example 6
[0101] (1) The titanium substrate was ultrasonically cleaned in acetone, ethanol, and deionized water for 5 minutes each, and then treated with a 5% (v / v) hydrofluoric acid dilute solution for 4 minutes. The titanium substrate was used as the anode, graphite was used as the cathode, and the electrolyte was a mixed aqueous solution of ammonium fluoride and ammonium sulfate (ammonium sulfate concentration was 5 mol / L, ammonium fluoride concentration was 2 wt%, pH value was 5). The anodization was performed for 30 minutes at a voltage of 20 V and an electrode spacing of 5 cm. After the reaction was completed, the titanium substrate was cleaned with ethanol and dried in a drying oven at 60° C. to prepare a titanium substrate with an in-situ constructed TiO2 nanotube array layer on the surface;
[0102] (2) Dissolving IL-4 (PeproTech, catalog number: 214-14) in a PBS buffer solution containing 5% trehalose to prepare an IL-4 solution with a concentration of 0.1 μg / mL; placing the titanium substrate with an in-situ constructed TiO2 nanotube array layer on the surface obtained in step (1) in a vacuum desiccator, dripping 50 μL of the IL-4 solution on the surface, and vacuuming the TiO2 nanotubes to absorb the IL-4 into the interior; repeating the steps of dripping the IL-4 solution and absorbing the TiO2 nanotubes once to obtain a titanium-based implant loaded with IL-4;
[0103] (3) Dissolve mPEG2000-PLGLAG-(PEG4)-C (Shanghai Qiangyao Biotechnology Co., Ltd., catalog number: 04010077270) in deionized water to prepare a solution with a concentration of 400 μM, immerse the titanium-based implant loaded with IL-4 in step (2) in the mPEG2000-PLGLAG-(PEG4)-C solution, and react for 12 h at room temperature (26°C) in the dark. After the reaction, wash with deionized water for 3 min and blow dry with nitrogen to prepare an anti-inflammatory and osteogenic titanium-based implant with an IL-4 loading of 1.53 ng / cm 2 ; The grafting amount of mPEG2000-PLGLAG-(PEG4)-C is 147.71 molecules / nm 2 .
[0104] The surface morphology of the titanium nanotubes in the anti-inflammatory and osteogenic titanium-based implant of Example 6 was observed by scanning electron microscopy. Fig.16 , Fig.17 As shown, the average diameter of the nanotubes is 37.94 nm and the depth is 357.31 nm.
[0105] The anti-inflammatory and osteogenic titanium-based implant of Example 6 was subjected to IL-4 release rate test and anti-inflammatory effect test. The test method was the same as that of Example 1. The results showed that it was able to respond to the MMP of the surrounding microenvironment to regulate the release of IL-4, inhibit the M1 polarization of macrophages, reduce the generation of ROS, and have an anti-inflammatory effect.
[0106] Example 7
[0107] (1) The titanium substrate was ultrasonically cleaned in acetone, ethanol, and deionized water for 5 minutes each, and then treated with a 5% (v / v) dilute hydrofluoric acid solution for 4 minutes. The titanium substrate was used as an anode, graphite was used as a cathode, and the electrolyte was a mixed aqueous solution of ammonium fluoride and ammonium sulfate (ammonium sulfate concentration was 5 mol / L, ammonium fluoride concentration was 1 wt%, pH value was 5). The anodization was performed for 120 minutes at a voltage of 5 V and an electrode spacing of 5 cm. After the reaction was completed, the titanium substrate was cleaned with ethanol and dried in a drying oven at 60° C. to prepare a titanium substrate with an in-situ constructed TiO2 nanotube array layer on the surface;
[0108] (2) Dissolving IL-4 (PeproTech, catalog number: 214-14) in a PBS buffer solution containing 5% trehalose to prepare an IL-4 solution with a concentration of 0.5 μg / mL; placing the titanium substrate with an in-situ constructed TiO2 nanotube array layer on the surface obtained in step (1) in a vacuum desiccator, dripping 50 μL of the IL-4 solution on the surface, and applying vacuum to absorb the IL-4 into the TiO2 nanotubes; repeating the steps of dripping the IL-4 solution and absorbing it into the TiO2 nanotubes twice to obtain a titanium-based implant loaded with IL-4;
[0109] (3) Dissolve mPEG2000-PLGLAG-(PEG4)-C (Shanghai Qiangyao Biotechnology Co., Ltd., catalog number: 04010077270) in deionized water to prepare a solution with a concentration of 50 μM, immerse the titanium-based implant loaded with IL-4 in step (2) in the mPEG2000-PLGLAG-(PEG4)-C solution, and react for 6 h at room temperature (26°C) in the dark. After the reaction, wash with deionized water for 3 min and blow dry with nitrogen to prepare an anti-inflammatory and osteogenic titanium-based implant with an IL-4 loading of 9.58 ng / cm 2 ; The grafting amount of mPEG2000-PLGLAG-(PEG4)-C is 5.73 molecules / nm 2 .
[0110] The surface morphology of the titanium nanotubes in the anti-inflammatory and osteogenic titanium-based implant of Example 7 was observed by scanning electron microscopy. Fig.18 , Fig.19 As shown, the average diameter of the nanotubes is 7.28 nm and the depth is 156.7 nm.
[0111] The anti-inflammatory and osteogenic titanium-based implant of Example 7 was subjected to IL-4 release rate test and anti-inflammatory effect test. The test method was the same as that of Example 1. The results showed that it was able to respond to the MMP of the surrounding microenvironment to regulate the release of IL-4, inhibit the M1 polarization of macrophages, reduce the generation of ROS, and have an anti-inflammatory effect.
[0112] Example 8
[0113] (1) The titanium substrate was ultrasonically cleaned in acetone, ethanol, and deionized water for 5 minutes each, and then treated with a 5% (v / v) dilute hydrofluoric acid solution for 4 minutes. The titanium substrate was used as an anode, graphite was used as a cathode, and the electrolyte was a mixed aqueous solution of ammonium fluoride and ammonium sulfate (ammonium sulfate concentration was 4 mol / L, ammonium fluoride concentration was 1 wt%, pH value was 5). The anodization was performed for 90 minutes at a voltage of 20 V and an electrode spacing of 5 cm. After the reaction was completed, the titanium substrate was cleaned with ethanol and dried in a drying oven at 60° C. to prepare a titanium substrate with an in-situ constructed TiO2 nanotube array layer on the surface;
[0114] (2) Dissolving IL-4 (PeproTech, catalog number: 214-14) in a PBS buffer solution containing 5% trehalose to prepare an IL-4 solution with a concentration of 2 μg / mL; placing the titanium substrate with an in-situ constructed TiO2 nanotube array layer on the surface obtained in step (1) in a vacuum desiccator, dripping 50 μL of the IL-4 solution on the surface, and applying vacuum to absorb the IL-4 into the TiO2 nanotubes; repeating the steps of dripping the IL-4 solution and absorbing it into the TiO2 nanotubes once to obtain a titanium-based implant loaded with IL-4;
[0115] (3) Dissolve mPEG2000-PLGLAG-(PEG4)-C (Shanghai Qiangyao Biotechnology Co., Ltd., catalog number: 04010077270) in deionized water to prepare a solution with a concentration of 500 μM, immerse the titanium-based implant loaded with IL-4 in step (2) in the mPEG2000-PLGLAG-(PEG4)-C solution, and react for 8 h at room temperature (26°C) in the dark. After the reaction, wash with deionized water for 3 min and blow dry with nitrogen to prepare an anti-inflammatory and osteogenic titanium-based implant with an IL-4 loading of 25.65 ng / cm 2 ; The grafting amount of mPEG2000-PLGLAG-(PEG4)-C is 99.50 molecules / nm 2 .
[0116] The surface morphology of the titanium nanotubes in the anti-inflammatory and osteogenic titanium-based implant of Example 8 was observed by scanning electron microscopy. Fig. 20 , Fig.21 As shown, the average diameter of the nanotubes is 59.16 nm and the depth is 1221.36 nm.
[0117] The anti-inflammatory and osteogenic titanium-based implant of Example 8 was subjected to IL-4 release rate test and anti-inflammatory effect test. The test method was the same as that of Example 1. The results showed that it was able to respond to the MMP of the surrounding microenvironment to regulate the release of IL-4, inhibit the M1 polarization of macrophages, reduce the generation of ROS, and have an anti-inflammatory effect.
[0118] Example 9
[0119] (1) The titanium substrate was ultrasonically cleaned in acetone, ethanol, and deionized water for 5 minutes each, and then treated with a 5% (v / v) dilute hydrofluoric acid solution for 4 minutes. The titanium substrate was used as an anode, graphite was used as a cathode, and the electrolyte was a mixed aqueous solution of ammonium fluoride and ammonium sulfate (ammonium sulfate concentration was 3 mol / L, ammonium fluoride concentration was 0.1 wt%, pH value was 5). The anodization was performed for 60 minutes at a voltage of 30 V and an electrode spacing of 5 cm. After the reaction was completed, the titanium substrate was cleaned with ethanol and dried in a drying oven at 60° C. to prepare a titanium substrate with an in-situ constructed TiO2 nanotube array layer on the surface;
[0120] (2) Dissolving IL-4 (PeproTech, catalog number: 214-14) in a PBS buffer solution containing 5% trehalose to prepare an IL-4 solution with a concentration of 50 μg / mL; placing the titanium substrate with an in-situ constructed TiO2 nanotube array layer on the surface obtained in step (1) in a vacuum desiccator, dripping 50 μL of the IL-4 solution on the surface, and vacuuming the TiO2 nanotubes to absorb the IL-4 into the interior; repeating the steps of dripping the IL-4 solution and absorbing the TiO2 nanotubes five times to obtain a titanium-based implant loaded with IL-4;
[0121] (3) Dissolve mPEG2000-PLGLAG-(PEG4)-C (Shanghai Qiangyao Biotechnology Co., Ltd., catalog number: 04010077270) in deionized water to prepare a solution with a concentration of 50 μM, immerse the titanium-based implant loaded with IL-4 in step (2) in the mPEG2000-PLGLAG-(PEG4)-C solution, and react for 3 h at room temperature (26°C) in the dark. After the reaction, wash with deionized water for 3 min and blow dry with nitrogen to prepare an anti-inflammatory and osteogenic titanium-based implant with a loading amount of IL-4 of 3.73 μg / cm 2 ; The grafting amount of mPEG2000-PLGLAG-(PEG4)-C is 1.05 molecules / nm 2 .
[0122] The surface morphology of the titanium nanotubes in the anti-inflammatory and osteogenic titanium-based implant of Example 9 was observed by scanning electron microscopy. Fig. 22 , Fig.23 As shown, the average diameter of the nanotubes is 103.26 nm and the depth is 527.3 nm.
[0123] The anti-inflammatory and osteogenic titanium-based implant of Example 9 was subjected to IL-4 release rate test and anti-inflammatory effect test. The test method was the same as that of Example 1. The results showed that it was able to respond to the MMP of the surrounding microenvironment to regulate the release of IL-4, inhibit the M1 polarization of macrophages, reduce the generation of ROS, and have an anti-inflammatory effect.
[0124] Example 10
[0125] (1) The titanium substrate was ultrasonically cleaned in acetone, ethanol, and deionized water for 5 minutes each, and then treated with a 5% (v / v) dilute hydrofluoric acid solution for 4 minutes. The titanium substrate was used as an anode, graphite was used as a cathode, and the electrolyte was a mixed aqueous solution of ammonium fluoride and ammonium sulfate (ammonium sulfate concentration was 2 mol / L, ammonium fluoride concentration was 0.5 wt%, pH value was 5). The anodization was performed for 30 minutes at a voltage of 30 V and an electrode spacing of 5 cm. After the reaction was completed, the titanium substrate was cleaned with ethanol and dried in a drying oven at 60° C. to prepare a titanium substrate with an in-situ constructed TiO2 nanotube array layer on the surface;
[0126] (2) Dissolving IL-4 (PeproTech, catalog number: 214-14) in a PBS buffer solution containing 5% trehalose to prepare an IL-4 solution with a concentration of 200 μg / mL; placing the titanium substrate with an in-situ constructed TiO2 nanotube array layer on the surface obtained in step (1) in a vacuum desiccator, dripping 50 μL of the IL-4 solution on the surface, and vacuuming the IL-4 to absorb it into the TiO2 nanotubes; repeating the steps of dripping the IL-4 solution and absorbing it into the TiO2 nanotubes 20 times to obtain a titanium-based implant loaded with IL-4;
[0127] (3) Dissolve mPEG2000-PLGLAG-(PEG4)-C (Shanghai Qiangyao Biotechnology Co., Ltd., catalog number: 04010077270) in deionized water to prepare a solution with a concentration of 100 μM, immerse the titanium-based implant loaded with IL-4 in step (2) in the mPEG2000-PLGLAG-(PEG4)-C solution, and react for 5 h at room temperature (26°C) in the dark. After the reaction, wash with deionized water for 3 min and blow dry with nitrogen to prepare an anti-inflammatory and osteogenic titanium-based implant, with an IL-4 loading of 42.56 μg / cm 2 ; The grafting amount of mPEG2000-PLGLAG-(PEG4)-C is 11.15 molecules / nm 2 .
[0128] The surface morphology of the titanium nanotubes of the anti-inflammatory and osteogenic titanium-based implant of Example 10 was observed by scanning electron microscopy. Fig.24 , Fig.25As shown, the average diameter of the nanotubes is 34.15 nm and the depth is 917.9 nm.
[0129] The anti-inflammatory and osteogenic titanium-based implant of Example 10 was subjected to IL-4 release rate test and anti-inflammatory effect test. The test method was the same as that of Example 1. The results showed that it was able to respond to the MMP of the surrounding microenvironment to regulate the release of IL-4, inhibit the M1 polarization of macrophages, reduce the generation of ROS, and have an anti-inflammatory effect.
[0130] Comparative Example 1
[0131] (1) The titanium substrate was ultrasonically cleaned in acetone, ethanol, and deionized water for 5 minutes each, and then treated with a 5% (v / v) dilute hydrofluoric acid solution for 4 minutes. The titanium substrate was used as an anode, graphite was used as a cathode, and the electrolyte was a mixed aqueous solution of ammonium fluoride and ammonium sulfate (ammonium sulfate concentration was 1 mol / L, ammonium fluoride concentration was 1 wt%, pH value was 5). The anodization was performed for 30 minutes at a voltage of 20 V and an electrode spacing of 5 cm. After the reaction was completed, the substrate was cleaned with ethanol and dried in a drying oven at 60° C. to prepare a titanium substrate with an in-situ constructed TiO2 nanotube array layer on the surface;
[0132] (2) Dissolve IL-4 (PeproTech, catalog number: 214-14) in PBS buffer containing 5% trehalose to prepare an IL-4 solution with a concentration of 1 μg / mL; place the titanium substrate with a TiO2 nanotube array layer in situ constructed on the surface obtained in step (1) in a vacuum desiccator, drip 50 μL of IL-4 solution on the surface, and draw a vacuum to absorb IL-4 into the TiO2 nanotubes; repeat the steps of dripping IL-4 solution and absorbing it into the TiO2 nanotubes three times to obtain a titanium-based implant loaded with IL-4; the IL-4 loading amount is 49.50 ng / cm 2 .
[0133] IL-4 release rate test of titanium-based implants:
[0134] The titanium-based implant of Comparative Example 1 was immersed in PBS solution and placed on a constant temperature shaker (37°C, 85 rpm). 1 mL of the solution was taken as the test sample at specific time points of 1, 2, 4, 10, 24, 48, 72, 96, 120, 144, 168, 192, 216, 240, 264, 288, 312, and 336 h, and the IL-4 release of the titanium-based implant at each time point was determined using an ELISA kit. The results are shown in FIG. Fig.26 As shown, it can be seen that the IL-4 release of the titanium-based implant increases rapidly from 0 hours, indicating that the titanium-based implant of Comparative Example 1 cannot effectively regulate the release of IL-4 and has no dynamic regulatory effect on the immune response to bone healing.
[0135] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent transformations made using the contents of the present invention's specification and drawings, or directly or indirectly applied in related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. An anti-inflammatory and osteogenic titanium-based implant, characterized in that: The invention comprises a titanium substrate; a TiO2 nanotube array layer is in-situ constructed on the surface of the titanium substrate; IL-4 is loaded in the TiO2 nanotube array layer, and a gate molecule mPEG2000-PLGLAG-(PEG4)-C is grafted on the surface of the TiO2 nanotube array layer; The structural formula of the gate molecule mPEG2000-PLGLAG-(PEG4)-C is as follows:
2. The anti-inflammatory and osteopromoting titanium-based implant according to claim 1, characterized in that: The average diameter of the TiO2 nanotubes in the TiO2 nanotube array layer is 7-110nm, and the depth of the nanotubes is 150-1250nm.
3. The anti-inflammatory and osteopromoting titanium-based implant according to claim 1, characterized in that: The average diameter of the TiO2 nanotubes in the TiO2 nanotube array layer is 40-90nm, and the depth of the nanotubes is 350-700nm.
4. The anti-inflammatory and osteopromoting titanium-based implant according to claim 1, characterized in that: The loading amount of IL-4 was 1.53 ng / cm 2 -42.56μg / cm 2 ; The grafting amount of mPEG2000-PLGLAG-(PEG4)-C is 1.05 molecules / nm 2 -259.50 molecules / nm 2 .
5. The anti-inflammatory and osteopromoting titanium-based implant according to claim 1, characterized in that: The gate molecule mPEG2000-PLGLAG-(PEG4)-C is grafted onto the surface of the TiO2 nanotube array layer through the reaction of thiol and titanium hydroxyl.
6. The method for preparing the anti-inflammatory and osteogenic titanium-based implant according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) In-situ construction of a TiO2 nanotube array layer on the surface of a titanium substrate by anodization; (2) preparing an IL-4 solution, dripping the IL-4 solution onto the surface of the TiO2 nanotube array layer on the titanium substrate, and absorbing the IL-4 solution into the interior of the TiO2 nanotubes using a negative pressure drug loading method to obtain a titanium-based implant loaded with IL-4; (3) preparing mPEG2000-PLGLAG-(PEG4)-C solution, immersing the IL-4 loaded titanium-based implant in the mPEG2000-PLGLAG-(PEG4)-C solution, and reacting in the dark. After the reaction is completed, washing and drying are performed to prepare an anti-inflammatory and osteopromoting titanium-based implant.
7. The method for preparing the anti-inflammatory and osteopromoting titanium-based implant according to claim 6, characterized in that: In the step (1), the anodizing method comprises the following steps: using a titanium substrate as an anode, graphite as a cathode, and an electrolyte being a mixed aqueous solution of ammonium fluoride and ammonium sulfate, performing anodizing at a constant voltage, and after the reaction is completed, washing and drying to prepare a titanium substrate with an in-situ constructed TiO2 nanotube array layer on the surface; wherein the ammonium sulfate concentration of the electrolyte is 0.5-5 mol / L, the ammonium fluoride concentration is 0.1-2 wt%, and the pH value of the electrolyte is 4-6; the anodizing voltage is 5-30 V, the electrode spacing is 2-10 cm, and the reaction time is 0.5-2 h.
8. The method for preparing the anti-inflammatory and osteopromoting titanium-based implant according to claim 6, characterized in that: In step (2), the preparation method of the IL-4 solution comprises the following steps: dissolving IL-4 in a PBS buffer solution containing 5% trehalose to prepare an IL-4 solution with a concentration of 0.1-200 μg / mL; The negative pressure drug loading method is to use a vacuum dryer to draw a vacuum so that the IL-4 solution is absorbed into the interior of the TiO2 nanotubes.
9. The method for preparing the anti-inflammatory and osteopromoting titanium-based implant according to claim 6, characterized in that: In the step (3), the preparation method of the mPEG2000-PLGLAG-(PEG4)-C solution comprises the following steps: dissolving mPEG2000-PLGLAG-(PEG4)-C with deionized water to prepare a mPEG2000-PLGLAG-(PEG4)-C solution with a concentration of 50-200 μM; The light-proof reaction time is 1-12 hours.
10. Use of the anti-inflammatory osteogenic titanium-based implant according to any one of claims 1 to 5 in the preparation of bone repair materials.
Citation Information
Cited By
Implant surface modification method for diabetic bone repair
CN121102581A